Analysis of Implementations Inclusive Education in Surabaya City - Sudarto, Zaini; Sasongko, Tri Budi (Jurusan Pendidikan Luar Biasa)
AbstrakImplementasi Pendidikan inklusifÂ di kota Surabaya telah di awali sejak tahun 2009 hingga saat ini tahun 2020, yaitu di 20 SD Kota Surabaya hingga sekarang berjumlah 50 SD Negeri dan 5 SD swasta, 20 SMP Negeri, 3 SMP Swasta, serta 2 SMA Negeri dan 2 SMK Negeri. Â Pemkot Surabaya juga memberikan perhatian lebih untuk sekolah inklusi dan layanan khusus, dengan memberikan peralatan yang dibutuhkan, seperti guru pendamping, psikolog, fasilitas kursi roda, komputer braille, alat musik, dan lain sebagainya. Pelaksanaan Penelitian dalam Rangka analisis penyelenggaraan Pendidikan Inklusif di Sekolah SDN se Kota Surabaya sudah mencapai 75%, yaitu telah melaksanakan persiapan materi, persiapan instrumen, koordinasi dengan subyek penelitian yang telah ditentukan.Kata Kunci: Pendidikan, Inklusif, SurabayaÂ AbstractThe implementation of inclusive education in the city of Surabaya has been initiated since 2009 until now in 2020, namely in 20 SD in the City of Surabaya until now there are 50 public SDs and 5 private SDs, 20 State SMPs, 3 Private SMPs, and 2 Public SMAs and 2 SMKs. Country. The Surabaya City Government also pays more attention to inclusive schools and special services, by providing the necessary equipment, such as accompanying teachers, psychologists, wheelchair facilities, braille computers, musical instruments, and so on. Research implementation in the framework of analyzing the implementation of Inclusive Education in SDN Schools throughout Surabaya has reached 75%, namely having carried out material preparation, instrument preparation, coordination with predetermined research subjects.Keyword: Education, Inclusive, Surabaya